Dampak Kecerdasan Emosional Dan Kompensasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening - Akbar, Tarmizi; Syahril; Rohman, Abdul; Oruw, Arikus; Subhan; Mulyadi, Edi (Jurnal Teknologi dan Bisnis Cerdas, 2025)
This study aims to analyze the effect of emotional intelligence and compensation on employee performance, with job satisfaction as a mediating variable, in the financial and banking sector in Bandung City, Indonesia. A quantitative approach using a survey method was employed, involving 170 respondents selected through purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that emotional intelligence and compensation have a positive and significant effect on both job satisfaction and employee performance. Job satisfaction significantly mediates the relationship between emotional intelligence and compensation on employee performance. The mediation effect indicates that enhancing emotional intelligence and providing fair compensation can optimally improve performance when accompanied by high job satisfaction. These results emphasize the importance of developing emotional intelligence through training and implementing fair compensation systems to increase employee motivation, loyalty, and productivity.